2002
DOI: 10.1016/s0048-9697(01)01073-7
|View full text |Cite
|
Sign up to set email alerts
|

Metal contamination at a wood preservation site: characterisation and experimental studies on remediation

Abstract: The aim of this investigation was to determine the occurrence of As, Cu, Cr and Zn in the soil at an abandoned wood preservation unit and to examine some possible extractants for the contaminants in the soil. The mean As content of the contaminated surface soils (0-10 cm) was 186 mg kg , where as the mean concentrations of Cu, Cr y1 and Zn in soils from the contaminated area were 26, 29 and 91 mg kg , respectively. The elevated As content in y1 the mineral soils is related to adsorption of inorganic As phases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
52
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(68 citation statements)
references
References 40 publications
9
52
1
2
Order By: Relevance
“…Bien qu'ils soient efficaces, ils sont souvent nocifs à l'homme et à l'environnement. Les produits les plus employés étaient, le chromate acide de cuivre (CCA), l'arséniate de cuivre chromé (ACC) et l'arséniate de cuivre et zinc (ACZA), des fongicides dont l'usage est de plus en plus restreint en raison de leur grande toxicité (Lund & Fobian, 1991 ;Andersen et al, 1996 ;Stilwell & Gorny, 1997 ;Deferera et al, 2000 ;Hingston et al, 2001 ;Bhattacharya et al, 2002). Pour faire face à cette problématique, il devient de plus en plus indispensable de remplacer ces produits chimiques par des produits qui respectent l'environnement (Schultz & Nicholas, 2000).…”
Section: Introductionunclassified
“…Bien qu'ils soient efficaces, ils sont souvent nocifs à l'homme et à l'environnement. Les produits les plus employés étaient, le chromate acide de cuivre (CCA), l'arséniate de cuivre chromé (ACC) et l'arséniate de cuivre et zinc (ACZA), des fongicides dont l'usage est de plus en plus restreint en raison de leur grande toxicité (Lund & Fobian, 1991 ;Andersen et al, 1996 ;Stilwell & Gorny, 1997 ;Deferera et al, 2000 ;Hingston et al, 2001 ;Bhattacharya et al, 2002). Pour faire face à cette problématique, il devient de plus en plus indispensable de remplacer ces produits chimiques par des produits qui respectent l'environnement (Schultz & Nicholas, 2000).…”
Section: Introductionunclassified
“…The source of arsenic may be the erosion of natural deposits, runoff from orchards, and runoff from industrial and municipal wastes. Anthropogenic activities also intensified the As contamination in water by several means such as processing and combustion of fossil fuels, production and use of arsenical pesticides in agriculture, and incineration and disposal of industrial and municipal wastes [62,63]. From these sources, As releases to the soil -especially in the form of pesticides and solid waste, from which its soluble forms ultimately leach out to the ground water [64].…”
mentioning
confidence: 99%
“…Elliott and Shastri (1999) reported that the overall extent of metal solubilization increased modestly as the system became more acidic. Other researchers suggested low molecular weight organic acid and phosphate salts were more effective in Log(BCF-1M NH4NO3) = 1.511+1.156Log(Na) 0.62*** <0.000 **(P<0.01), ***(P<0.001) extracting As, attaining more than 40% extraction in the pH range of 6~8 (Alam et al, 2001;Bhattacharya et al, 2002;Stroud et al, 2011). Bioconcentration factors (BCF) of soil to rice according to various single extracting solutions are shown in Table 5.…”
Section: Arsenic Contents In Soils Using Single Extraction Methodsmentioning
confidence: 96%